Environmental management practices in the SME hospitality industry: Mediating impact of managers' commitment to institutional pressures and EMS implementation. / Hanafi Hamzah ...[et al.] - Hamzah, Hanafi; Ab. Karim, Muhammad Shahrim; Abdul Aziz, Yuhanis; Kasim, Azilah (Universiti Teknologi MARA, 2021)
Despite the growing concern for Environmental Management Systems (EMS) in the hospitality industry, the relationship between institutional pressures and environmental management implementation is rarely examined in the small- and medium-scale enterprise hotels (SMEHs) context. Concerning the impact of tourism activities on the environment has been increasing; unfortunately, many hotels are unwilling to develop an EMS, probably due to a lack of resources and knowledge. Little attention has been devoted, especially among the SMEHs in Malaysia. The primary purpose of this study was to investigate the effects of institutional pressures on the SMEH environmental management implementation in addition to determining the manager's commitment as mediating factor. Quantitative research was conducted in this study to establish how managers deal with specific situations using the environmental management system. A total of 313 managers were randomly selected from a total of 1695 registered SMEHs in Malaysia. The results were analyzed using Partial Lease Square-Structural Equation Modeling (PLS-SEM) software version 3.2.8 to validate the proposed model and Bootstrapping test to determine the mediation effects of the manager's perceived benefits and commitment. The initial observation suggested that the majority of the managers implemented the environmental management system were due to regulatory pressures and customer's pressures. Meanwhile, a smaller group of managers were also keen on the EMS implementation due to their attributes in which they are well aware of the benefits of the system. However, the business owners were found to have relatively low engagement with the environmental agenda. This research aims to contribute to the management and operation advancement towards developing thinking, practice and research within the SMEH industry in Malaysia. Therefore, the findings of this study could provide a framework for assessing existing SMEH industry perceptions and willingness to implement the EMS for a better and sustainable hospitality practice, especially from the decision makers' point of view.